Interpretive Internalism In The Time Of Technoscience (Sociología y Tecnociencia, 2017)
This paper argues that scientific inquiry (1) creates its own cognitive autonomy within the interplay of research practices and possibilities for doing research, and (2) discloses, meaningfully articulates, and procedurally objectifies reality in a unique manner. Taken together, both claims characterize the position of hermeneutic realism which lays foundations for the radically anti-foundationalist hermeneutic philosophy of science. Claim (1) opens a subject of meta-epistemological studies aiming at a complementarity between a hermeneutic theory of the facticity of scientific inquiry as a mode of being and an epistemological theory that works out in its own terms the conditions for having science’s cognitive specificity, whereas claim (2) is a necessary presupposition for studying how reality becomes meaningfully articulated within scientific practices. The position of hermeneutic realism is on a par with the thesis of interpretive internalism stating that the cognitive autonomy of scientific inquiry is achieved through the openness of inquiry to its milieus. This openness consists in a selective assimilation of external themes, goals, tasks, and other items. The paper also deals with some socio-political consequences from the thesis of interpretive internalism. It is argued that only scientific inquiry freed from social monitoring and political control is able to serve societal needs, preventing at the same time a politically initiated scientification of societies, i.e. a scientification guided by dubious economic and political interests, and accomplished through sciences that are not able to preserve their cognitive autonomy, thereby becoming exposed to manipulation and misuse.